Effect of Floating Offshore Wind Turbines on Atmospheric Circulation in California - Raghukumar, Kaustubha; Chartrand, Chris; Chang, Grace; Cheung, Lawrence; Roberts, Jesse (Frontiers in Energy Research, 2022)
In California offshore waters, sustained northwesterly winds have been identified as a key energy resource that could contribute substantially to California’s renewable energy mandate. It is these winds that drive upwelling, which is responsible for much of the primary productivity that sustains one of the richest ecosystems on the planet. The goal of this study is to quantify changes in wind stress at the sea surface as the result of offshore wind turbine deployments by use of an atmospheric model. Results from this study will inform future ocean circulation modeling. The Weather Research and Forecasting model was implemented on a regional scale along the U.S. west coast, with a higher resolution nest along the California continental shelf. Simulated arrays of offshore wind turbines were placed within call areas for wind farm development offshore of Central and Northern California. At full build-out, it was found that wind stress magnitudes at 10 m height are reduced by approximately 5%, with wakes extending approximately 200 km downwind of the nominated lease block areas. With the length scale of wind stress reductions on the order of 250 km, several times the internal Rossby radius of deformation, it is hypothesized that a measurable effect on upwelling is possible.